Hadji Agus Salim's Islamic Feminism Thoughts and Its Contribution to Contemporary Islamic Studies - Ermagusti Ermagusti; Erwin Erwin; Rido Putra; Rahmad Tri Hadi (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2024)
This article explores the discourse on Islamic feminism through the perspective of H. Agus Salim. Using a descriptive-analytical method and an Islamic feminist approach rooted in harmony and justice—distinct from Western notions of equality—the study examines Salim’s works as primary sources, supported by secondary materials such as books, journal articles, and online resources discussing his thought. The findings reveal: (1) Salim advocates for equality in rights and responsibilities between men and women, particularly in education; (2) he approaches the hijab with a contextual and historical understanding, considering asbab al-nuzul; (3) he views the veil not merely as a piece of cloth but as a potential symbol of oppression; (4) he favors monogamy over polygamy, emphasizing the challenges of achieving justice and the historical specificity of certain rulings; and (5) he acknowledges the inevitability of women assuming leadership roles. This study highlights Salim’s nuanced stance on gender issues within an Islamic framework.